Peta Tematik Pemetaan Penyebaran Barbershop Di Kelurahan Pisang Candi, Kecamatan Sukun, Kota Malang - Fransiskus Febrien; Ida Wahyuni (Jurnal Transformasi Digital Masyarakat (DIGIMAS), 2025)
In the area of ​​Pisang Candi Village, Sukun District, Malang City, the barbershop business has shown rapid progress in recent years. This can be seen from the increasing number of modern barbershops that have been established in various strategic locations. However, the lack of organized mapping of the distribution of barbershops hinders business development planning and regional spatial regulations. This study aims to examine the spatial distribution pattern of barbershops in Pisang Candi Village and identify the elements that influence the selection of their location. The method used is a descriptive quantitative approach, while data collection is carried out by utilizing location maps from Google Maps. In data analysis, we use Geographic Information Systems (GIS) through the QGIS application to create thematic maps. The research findings show that there are 20 barbershops that form a grouping pattern, especially along main roads and around educational areas. This mapping provides spatial information that can be used as a guide in planning the development of barbershop businesses and preparing spatial regulations in Pisang Candi Village.